2021
DOI: 10.3390/foods10040815
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Evaluation of the Antimicrobial and Antioxidant Potential of Mentha × smithiana R. GRAHAM Essential Oil from Western Romania

Abstract: This study was conducted to identify the volatile compounds of Mentha × smithiana essential oil (MSEO) and evaluate its antioxidant and antibacterial potential. The essential oil (EO) content was assessed by gas chromatography–mass spectrometry (GC-MS). Carvone (55.71%), limonene (18.83%), trans-carveol (3.54%), cis-carveol (2.72%), beta-bourbonene (1.94%), and caryophyllene oxide (1.59%) were the main identified compounds. The MSEO displayed broad-spectrum antibacterial effects and was also found to be the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 53 publications
6
25
0
Order By: Relevance
“…This could mean that even if a biological antioxidant effect could well be correlated to the synergistic activity of most compounds, the highest in vitro antioxidant effect related to xanthine oxidoreductase inhibition is actually attributed to minor-occurring molecules. Our results are consistent with previous in silico studies reported by our research group, where a monoterpene-rich Mentha smithiana EO gave similar results in terms of a proposed in vitro antioxidant activity by targeting xanthine oxidoreductase [67].…”
Section: In Silico Prediction Of a Protein Target-based Antioxidant Mechanism By Molecular Docking Analysissupporting
confidence: 93%
“…This could mean that even if a biological antioxidant effect could well be correlated to the synergistic activity of most compounds, the highest in vitro antioxidant effect related to xanthine oxidoreductase inhibition is actually attributed to minor-occurring molecules. Our results are consistent with previous in silico studies reported by our research group, where a monoterpene-rich Mentha smithiana EO gave similar results in terms of a proposed in vitro antioxidant activity by targeting xanthine oxidoreductase [67].…”
Section: In Silico Prediction Of a Protein Target-based Antioxidant Mechanism By Molecular Docking Analysissupporting
confidence: 93%
“…The molecular docking protocol employed in this study was previously reported [ 79 , 80 ]. Briefly, protein targets structures were available from the RCSB Protein Data Bank [ 81 ] ( Table 7 ).…”
Section: Methodsmentioning
confidence: 99%
“…The current molecular docking method used in this study was previously reported [97,98]. Briefly, protein target structures were retrieved from the RCSB Protein Data Bank [99] (Table 7).…”
Section: Molecular Dockingmentioning
confidence: 99%
“…For our current molecular docking protocol, we used PyRx v0.8 (The Scripps Research Institute, La Jolla, CA, USA), with Autodock Vina's embedded scoring function [100]. The docking method was validated as previously described [97]. The search space grid box was defined in terms of coordinates and size (Table 7) to best fit the active binding site of the native ligand.…”
Section: Molecular Dockingmentioning
confidence: 99%